2021
DOI: 10.1177/09612033211020367
|View full text |Cite
|
Sign up to set email alerts
|

The high expression of miR-564 in patients with systemic lupus erythematosus promotes differentiation and maturation of DC cells by negatively regulating TP53 expression in vitro

Abstract: Background miRNA is involved in the occurrence and progression of systemic lupus erythematosus (SLE), but the regulatory effect of miRNA on dendritic cells in SLE patients is still unclear. Material and methods Bioinformatics methods were used to analyze the differentially expressed miRNA and its target genes in SLE patients. In vitro experiments were conducted to explore the effects and mechanisms of differentially expressed miRNAs in SLE patients on the differentiation and maturation of monocyte-derived dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…TP53 is a central regulator of apoptosis [ 51 ], and its rs1042522G/C polymorphism is significantly associated with SLE in Chinese Han population [ 52 ]. Teng et al [ 53 ] revealed that the high expression of miR-564 in patients with SLE promoted differentiation of dendritic cells by negatively regulating TP53 expression.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 is a central regulator of apoptosis [ 51 ], and its rs1042522G/C polymorphism is significantly associated with SLE in Chinese Han population [ 52 ]. Teng et al [ 53 ] revealed that the high expression of miR-564 in patients with SLE promoted differentiation of dendritic cells by negatively regulating TP53 expression.…”
Section: Discussionmentioning
confidence: 99%